RNA localization during early development of the axolotl - Šimková, Kateřina; Naraine, Ravindra; Vintr, Jan; Soukup, Vladimír; Šindelka, Radek (Frontiers in Cell and Developmental Biology, 2023)
The asymmetric localization of biomolecules is critical for body plan development. One of the most popular model organisms for early embryogenesis studies is Xenopus laevis but there is a lack of information in other animal species. Here, we compare the early development of two amphibian species – the frog X. laevis and the axolotl Ambystoma mexicanum. This study aimed to identify asymmetrically localized RNAs along the animal-vegetal axis during the early development of A. mexicanum. For that purpose, we performed spatial transcriptome-wide analysis at low resolution, which revealed dynamic changes along the animal-vegetal axis classified into the following categories: profile alteration, de novo synthesis and degradation. Surprisingly, our results showed that many of the vegetally localized genes, which are important for germ cell development, are degraded during early development. Furthermore, we assessed the motif presence in UTRs of degraded mRNAs and revealed the enrichment of several motifs in RNAs of germ cell markers. Our results suggest novel reorganization of the transcriptome during embryogenesis of A. mexicanum to converge to the similar developmental pattern as the X. laevis